Borobudur Story Relief, A Silent Visual Narration - Primadi Tabrani (Wimba : Jurnal Komunikasi Visual, 2013)
Our research team found out that prehistory, primitive, traditional and children drawings havenearly the "same" visual language. It uses a different system of drawing then ours. We call these drawings as the 'Introductory' phase of drawing history. Their visuals have its 'grammar', so like in word language, visual language can tell stories. Both have time dimension needed for telling stories. So drawings from the 'introductory' phase are one picture that tells a story. This is one picture silent sequence that can have some scenes, without grids, without texts. This is in tune with Einstein General Relativity Theory (1916), which state that time and space cannot be separated, it is one entity. For a plane Einstein named it STP (Space "“ Time "“ Plane). In tune with it, this writer calls this 'new' system of drawing as the STP system of drawing. It has several modes, as: the Pradaksina, most characteristic view, multiple view, multiple time and place, twin, layers, film scene, X ray, make larger, make smaller, no perspective, no frame, no zoom ins/outs, etc. The onlookers can 'read' their pictures, because the artist and the onlookers use the same visual language. It is not a 'dead' still picture like a photo without time dimension, it is a 'living' still picture, which have time dimension.